Adsorption and photocatalytic removal of Ibuprofen by activated carbon impregnated with TiO2 by UV–Vis monitoring. (February 2019) - Gu, Ying; Yperman, Jan; Carleer, Robert; D'Haen, Jan; Maggen, Jens; Vanderheyden, Sara; Vanreppelen, Kenny; Garcia, Roberto Machado
Abstract: The removal of Ibuprofen was investigated by activated carbon impregnated with TiO2 . Emphasis was given on the effect of different parameters, such as composite type, initial Ibuprofen concentration (5–25 mg/L), temperature (22–28 °C) and pH (acidic and alkaline solution). The experiment was carried out in a self-made tubular flow reactor, with one 15 W monochromatic UV lamp (254 nm). The composite AC90T10 gives the highest removal degree of 92% of Ibuprofen solution under UV light within 4 h, due to synergy of adsorption and photodegradation. It was found that weight ratio of composite/Ibuprofen has limited effect on the removal degree within the concentration range (5–25 mg/L), but reaction time under UV light (4 h) and pH (acidic solution) are very important. The kinetic experimental data obtained at pH 4.3 at 25 °C on different composites were fitted to pseudo-first, pseudo-second and Elovich models, obtaining a high accuracy based on R 2 values. From the results, composites of granular activated carbon and TiO2 can enhance removal of Ibuprofen effectively, making recycle process much easier and less costly, which can be a promising method in future water treatment. Highlights: Three kinds of activated carbon impregnated with TiO2 (ACT) were prepared. Removal of Ibuprofen includes effects of adsorption and photodegradation by ACT. ACT composites effectively improve removal of Ibuprofen under UV. Kinetic tests of Ibuprofen removal were studied onto different composite catalysts.